PEMBUATAN PUPUK ORGANIK DARI LIDAH BUAYA DAN MANFAATNYA BAGI TANAMAN - Yayuk Minta Wahyuningsih; Zuraida; Bahrun (Fakultas Pertanian UVAYA Banjarmasin, 2024)
The Aloe Vera plant is a plant that grows in tropical climates. The aloe vera plant has 2 layers, namely latex, which is aloe vera that can be processed into organic fertilizer containing the nutrients N, P, K, Ca and Mg so that the aloe vera waste has the opportunity to be used as a source of nutrients for plants, besides being able to provide soil moisture, it also can improve the physico-chemical properties of soil. The Aloe Vera plant contains the hormones auxin and gibberellin which help speed up the development of roots, stems and leaves. The Aloe Vera plant also acts as a growth stimulant (ZPT) in the form of auxin and gibberellin. You can give it to the plant 2-3 times a week to get maximum results and accelerate growth of roots, stems, leaves and flowers. Aloe Vera plants can produce oxygen at night and do not require much care and contain NPK artificial fertilizer in liquid or solid coarse granular form. Apart from being beautiful and improving the aesthetics of the room, it can also help maintain indoor air quality . The benefits for humans are that the aloe vera plant contains minerals, namely selenium, magnesium, calcium, sodium, manganese, zinc, copper, chromium. Minerals play an important role in managing the enzyme system in the body's metabolic flow to act as anti- oxidation. Benefits of the aloe vera plant for health and beauty Namely, it can lower blood sugar, cholesterol, reduce itching, acne, heal wounds and mask.